Grape seed and skin extract protects against acute chemotherapy toxicity induced by doxorubicin in rat red blood cells and plasma - Hamlaoui, Sonia; Mokni, Meherzia; Limam, Nadia; Carrier, Alice; Limam, Ferid; Amri, Mohamed; Marzouki, Lamjed; Aouani, Ezzedine (Bangladesh Journal of Pharmacology, 2012)
In this study, the protective role of grape seed and skin extract (GSSE) against doxorubicin-induced blood toxicity has been evaluated in rats. Rats were treated with the extract for 8 days and injected with doxorubicin (20 mg/kg) at the 4th day. At the end of the treatment, blood samples were collected for oxidative stress parameters determination and antioxidant enzymes. Doxorubicin increased erythrocytes and plasma malondialdehyde, free iron, H2O2 and carbonylation, decreased calcium and also decreased erythrocytes catalase, peroxidase and superoxide dismutase (specially the Fe isoform). Doxorubicin also decreased plasma catalase and superoxide dismutase (Cu/Zn and Fe isoforms) but increased peroxidase. Doxorubicin increased plasma alanine aminotransferase and aspartate aminotransferase but decreased them within erythrocytes. GSSE co-treatment counteracted almost all deleterious effects induced by doxorubicin. In conclusion, doxorubicin induced a pro-oxidative stress into rat erythrocytes and plasma and GSSE exerted antioxidant properties which can be attributed to free iron and calcium modulation.